[2+2] Photocycloaddition of 3‐Alkenyloxy‐2‐cycloalkenones: Enantioselective Lewis Acid Catalysis and Ring Expansion1. Issue 47 (22nd September 2014) - Brimioulle, Richard; Bach, Thorsten
Abstract By application of substoichiometric amounts (50 mol %) of a chiral Lewis acid, the intramolecular [2+2] photocycloaddition of the title compounds was achieved with high enantioselectivity (up to 94 % ee). Upon cleavage of the cyclobutane ring the resulting tricyclic products underwent ring‐expansion reactions under acidic conditions and formed anellated seven‐ or eight‐membered‐ring systems without racemization. The ring expansion could be combined with a diastereoselective reduction (triethylsilane) or allylation (allyltrimethylsilane) upon BF3 catalysis (48–87 % yield).